Lyndon Baines Johnson, president - Devaney, John. (New York : Walker, 1986)
Follows the life and career of the Texas politician who became the 36th president of the United States.
Includes index.
School Library Journal.
Kirkus Review.
7.0
5-8
Keywords: Johnson, Lyndon B., -- 1908-1973 -- Juvenile literature; Johnson, Lyndon B., -- 1908-1973.; Presidents -- United States -- Biography -- Juvenile literature; Presidents -- United States -- Biography; Presidents -- United States -- Biography